Maternal homeschooling after abandonment and violence: understanding pedagogical experiences in Peru’s soup kitchens - Holguin-Alvarez, Jhon; Manrique-Alvarez, Giovanna; Ruiz-Salazar, Jenny (Frontiers in Education, 2025)
We examined the critical stance adopted by 25 Peruvian mothers involved in a community meal programme serving individuals in extreme poverty, analysing their educational role within the household in the absence of paternal support before, during, and after the pandemic. This qualitative study focused on an atypical case in order to characterise the participants according to diverse social traits, including family abandonment, spousal abuse, the scarcity of resources associated with a low socioeconomic status, and the lack of formal employment. This involved engaging with community meal programmes across six districts of the city of Lima, where the participating women were encouraged to watch videos on the role of women over the course of a month of fieldwork. The retrospective analytical methodology employed focus group techniques, interviews with the participants, and an examination of the children’s academic performance as a measure of convergent analysis [2019–2023]. The critical dialogue among the mothers generated findings in which thematic codes emerged that were associated with categories such as personal experiences, decisive experiences, and experiences linked to continuity in schooling. From the mothers’ perspective, the evidence enabled an interpretation of maternal education as a form of practical, experience-based instruction within the home, independent of paternal input and grounded in activities related to emotional and behavioural regulation, the application of basic pedagogical practices, and the provision of care to mitigate the spread of certain illnesses. These family conditions facilitated the mothers’ ability to ensure the continuity of their children’s education and to respond assertively to the temporary changes brought about by the pandemic in both economic and health-related domains.